PENGARUH TEKNIK MIND MAPPING TERHADAP KETERAMPILAN BERBICARA PESERTA DIDIK KELAS IX SMP NEGERI 1 PARIAMAN - WIDIA, WINA; WULANDARI, ERIKA; AFNITA, AFNITA (Jurnal Ilmu Pendidikan Indonesia, 2019)
The purpose of this study was to determine the effect of using mind mapping techniques on speaking skills of class IX students of SMP Negeri 1 Pariaman. The instrument used in this study is the performance test. The data of this study is the score of the test results of students' speaking skills at the pretest and posttest. Data were analyzed by percentage formula, formula for calculating averages and t-test. The results of the study concluded the following three things. First, the speaking skills of class IX students at the pretest were more than qualified with an average value of 66.78%. Second, students' speaking skills at the time of posttest were in Good qualification Â with an average value of 81.78%. Third, the alternative hypothesis (1) was received at a significant level of 95% and dk = n-1 because tcount Ëƒ t table (7.23â€“1.71). In other words, the use of mind mapping techniques significantly influences the speaking skills of class IX students of SMP Negeri 1 Pariaman.